THE INFLUENCE OF PROJECT BASED LEARNING MODEL USING KWL CHART ON STUDENT PROCESS SCIENCE SKILLS IN PHYSICS LEARNING AT SMA NEGERI 2 LUBUK PAKAM - SHIDIQ, HANA SALSABILA; Kadri, Muhammad (Journal of Learning and Technology in Physics, 2024)
This study aims to determine the effect of the Project Based Learning model on high school students’ science process skills. The type of research used is a quasi experimental research design with a two group pretest posttest design. The population used was students of class XI MIA SMA Negeri 2 Lubuk Pakam, totaling 2 classes. The research sample consisted of two classes, the class taken was XI MIA I as the experimental class and XI MIA III as the control class. The instrument used is a science process skills test in the form of an essay consisting of 10 questions that hav been declared valid by the validator. Based on the results of the study, the average pretest score for the experimental class was 20,68 and the pretest for the control class 18,85. The results of testing the hypothesis showed that a significant value of 0,411 >  0,05 otherwise  is accepted or both classes have the same initial abilities. After applying the Project Based Learning model, the average posttest score of the experimental class was 77,68 and that of the control class was 64,71. The results of testing the hypothesis showed that a significant value of 0,00 < = 0,05, it is stated that  is accepted, meaning that there is a significant influence of the Project Based Learning model on student’s science process skills.